2020
DOI: 10.1155/2020/8814236
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Role of Protein Tyrosine Phosphatase 1B in Parkinson’s Disease via Antineuroinflammation and Neuroprotection In Vitro and In Vivo

Abstract: Parkinson’s disease (PD) is one of the most widespread neurodegenerative diseases. However, the currently available treatments could only relieve symptoms. Novel therapeutic targets are urgently needed. Several previous studies mentioned that protein tyrosine phosphatase 1B (PTP1B) acted as a negative regulator of the insulin signal pathway and played a significant role in the inflammation process. However, few studies have investigated the role of PTP1B in the central nervous system. Our study showed that sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…8 ). Interestingly, a few studies have shown that PTP1B has a pro-neuroinflammation ability through its enhancement of the release of TNF-α, iNOS, and IL-6 170 , 171 in the brain or GSK3β in PD. 172 Recently, PTP1B was demonstrated to have dual roles in modulating the inflammation response in alcoholic liver injury 173 and non-alcoholic fatty liver disease 174 through its modulation of the inflammatory response.…”
Section: The Signaling Pathways Regulated By the Protein Phosphatases...mentioning
confidence: 99%
“…8 ). Interestingly, a few studies have shown that PTP1B has a pro-neuroinflammation ability through its enhancement of the release of TNF-α, iNOS, and IL-6 170 , 171 in the brain or GSK3β in PD. 172 Recently, PTP1B was demonstrated to have dual roles in modulating the inflammation response in alcoholic liver injury 173 and non-alcoholic fatty liver disease 174 through its modulation of the inflammatory response.…”
Section: The Signaling Pathways Regulated By the Protein Phosphatases...mentioning
confidence: 99%
“…Therefore, blocking this enzyme is an attractive strategy to treat both diabetes and obesity, which represents an advantage over existing therapies to date. Furthermore, PTP1B has gained much attention in recent years since it is involved in other diseases such as Alzheimer’s [ 5 ], Parkinson’s disease [ 6 , 7 ], cardiovascular disorders [ 8 , 9 , 10 , 11 ], and malignant tumors [ 12 , 13 , 14 , 15 , 16 ]. This makes the development of PTP1B inhibitors even more interesting.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence have indicated that NOS-II regulates CXC chemokine production and has a regulatory effect on neutrophil accumulation in various acute inflammations [57][58][59][60]. Moreover, IFN-γ can enhance NOS-II expression in various cells [61][62][63][64]. We found that the expression of Cxcl1, Cxcl2, and Ifng was significantly enhanced in the liver after the APAP challenge.…”
Section: Discussionmentioning
confidence: 57%